Effect of polymer-based rotary file in root canal irrigation on smear layer removal: a SEM study - Masudi, Sam'an Malik (2011)
Introduction: Removing of smear layer is an essential step for endodontic success. Smear layer is composed of an amorphous layer of organic and inorganic materials. It acts as a physical barrier interfering with adhesion and penetration of the sealer into the dentinal tubule. The aim of this study was to compare the cleaning efficiency of smear layer removal on prepared root canal surfaces by using syringe irrigation method and polymer-based rotary file for fluid agitation under Scanning Electron Microscope (SEM).